Blue skies and red sunsets: Reliability of performance parameters of various p-n junction photovoltaic module technologies. Issue 1 (1st January 2019) - Meyer, Edson L.; Overen, Ochuko K.
Abstract: This research presents, discusses and compares the reliability of the performance characteristics of six different p-n junction photovoltaic module technologies under varying operating conditions. The six module technologies are: CuInSe2 (CIS), a-Si:H, a-Si:H/a-SiGe:H/a-SiGe:H (a-SiGe:H), edge-defined film-fed growth silicon (EFG-Si), multi-crystalline silicon (mc-Si) and single crystalline silicon (c-Si). A simple but accurate method is then used to determine the modules' qualities. The effect of temperature on module performance is then investigated and results compared. Here it was found that the lower quality thin-film technologies are not as temperature dependent as their crystalline counterparts. The influence of irradiance on module performance was also measured and compared for the different technologies. The a-Si:H technology was found to be at least 16% more efficient than the other module technologies at 169 W/m 2 . Under actual outdoor operating conditions, however, the reliability of the STC measurements is no longer useful. CIS performs relatively better at high air-mass values, corresponding to times when the sun is lower in the sky, that is, red sunsets. Under these outdoor conditions, irradiance, temperature and spectral changes affect module performance and this research successfully motivates the importance of considering all three factors to be of equal importance when analysing the reliability of outdoor performance parameters of photovoltaic modules.